Enhancing Critical Thinking through Podcast-Based Project Learning in EFL Listening and Speaking Courses - Kriswinahyu, Aprilia Dyah; Budiraharjo, Markus (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2026)
In the 21st century, individuals with critical thinking skills are highly valued. Therefore, it drives a shift in higher education instructional models aim at enhancing these skills. This study examined the impact of podcast-making as a Project-Based Learning (PjBL) activity on students' critical thinking skills in an English as a Foreign Language (EFL) context. Utilizing a sequential explanatory mixed-method approach, this study addressed: (1) To what extent did PjBL enhance students' critical thinking? (2) What characteristics of PjBL contributed to the enhancement of students’ critical thinking? The participants of this study included 57 second-semester students from the English Language Education Study Program enrolled in an Advanced Listening and Speaking course, with 5 students selected for qualitative interviews. The quantitative results of this study indicated a significant enhancement in students' critical thinking skills, with the mean score rising from 45.58 (before podcast-making) to 60.61 (after podcast-making). A paired-t-test revealed a significant difference (t(56) = -19.56, p <0.001). Then, the qualitive findings identified key PjBL characteristics such as complex problem-solving, evidence-based reasoning, and reflective practice as contributing factors to the enhancement of students’ critical thinking skills. This study provides empirical evidence supporting podcast-making as an effective tool for enhancing critical thinking in EFL higher education. The findings offer valuable insights for educators seeking innovative instructional models. Future research could explore deeper the role of technology in PjBL and its impact on developing specific skills like critical thinking.